Intramuscular Single-dose Toxicity Test of Bufonis venonum Pharmacopuncture in Sprague-Dawley Rats - Kwang-Ho Lee; Seung-Ho Sun; Jun-Sang Yu; Ki-Rok Kwon (Korean Pharmacopuncture Institute, 2015)
Objectives: Bufonis venonum (BV) is the dried white secretions of the auricular and skin glands of the toads Bufo bufo gargarizans or Bufo melanosticus Schneider. This study was performed to evaluate the toxicity of intramuscularly- administered Bufonis venonum pharmacopuncture (BVP) and to calculate its approximate lethality through a single-dose test with Sprague-Dawley (SD) rats. Methods: Twenty male and 20 female 6-week-old SD rats were injected intramuscularly with BVP or normal saline. The animals were divided into four groups with five female and five male rats per group: the control group injected with normal saline at 0.5 mL/animal, the low-dosage group injected with 0.125 mL/animal of BVP, the medium-dosage group injected with 0.25 mL/animal of BVP and the high-dosage group injected with 0.5 mL/animal of BVP. All injections were in the left thighs of the rats. After administration, we conducted clinical observations everyday and body weight measurements on days 3, 7 and 14 after the injection. We also carried out hematology, serum biochemistry, and histological observations on day 15 after treatment. Results: No mortalities were observed in any experimental group. No significant changes in weight, hematology, serum biochemistry, and histological observations that could be attributed to the intramuscular injection of BVP were observed in any experimental group. Conclusion: Lethal dose of BVP administered via intramuscular injection in SD rats is over 0.5 mL/animal.